2006
DOI: 10.1037/0022-0663.98.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instructional support within constructivist learning environments for elementary school students' understanding of "floating and sinking."

Abstract: In a repeated measures design (pretest, posttest, 1-year follow-up) with 161 3rd-grade students, the authors compared 2 curricula on floating and sinking within constructivist learning environments, varying in instructional support. The 2 curricula differed in the sequencing of content and the teacher's cognitively structuring statements. At the posttest, both instructed groups showed significant gains on a test on understanding the concepts of density and buoyancy force as compared to a baseline group without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
188
0
34

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(247 citation statements)
references
References 31 publications
(41 reference statements)
12
188
0
34
Order By: Relevance
“…The empirical findings in the last few years confirm the significance of instructional activity on the part of the teacher (e.g. findings from early scientific learning: Hardy et al 2006;Klahr & Nigam 2004) or make it clear that it is not primarily the observed activity of the learner, but rather the cognitive activation that the teacher's activity initiates in the learner that is decisive for successful cognitive learning processes (Meyer 2009). The meta-analysis by Alfieri et al (2011) of discovery learning shows that the approaches of guided discovery are superior to pure, unassisted discovery with regard to the efficiency of the acquisition of knowledge.…”
Section: The Dimension 'Free Activity and Instructed Activity' Basedsupporting
confidence: 48%
“…The empirical findings in the last few years confirm the significance of instructional activity on the part of the teacher (e.g. findings from early scientific learning: Hardy et al 2006;Klahr & Nigam 2004) or make it clear that it is not primarily the observed activity of the learner, but rather the cognitive activation that the teacher's activity initiates in the learner that is decisive for successful cognitive learning processes (Meyer 2009). The meta-analysis by Alfieri et al (2011) of discovery learning shows that the approaches of guided discovery are superior to pure, unassisted discovery with regard to the efficiency of the acquisition of knowledge.…”
Section: The Dimension 'Free Activity and Instructed Activity' Basedsupporting
confidence: 48%
“…Thus, it is important to distinguish misconceptions from incorrect remembering, as for example in remembering the order of the planets from the sun. Hardy, Jonen, Moller, and Stern (2006) studied misconceptions related to the concepts of density and buoyancy force in 161 third-grade students and found that the number of misconceptions was reduced as a function of instructional support. Two other examples are misconceptions in the comprehension of hierarchical graphs (Korner, 2005) and in the areas of politics and law (Janicki, 2006).…”
mentioning
confidence: 99%
“…Their approach is more towards constructivism, where they let the student generate their own idea through discussion and one to one learning. Constructivism can help students to explore new ideas and come up with creative solutions, apply cooperative learning with peers and encourage long time understanding (Hardy, Jonen, Moller & Stern, 2006). Teachers who apply constructivism paradigm for teaching and learning need to recognise their students' ability to learn, be creative in choosing teaching material and provide strong guidance for student learning (Kirschner, Sweller & Clark, 2006).…”
Section: ) Professional Orientationmentioning
confidence: 99%